Analyzing the Effect of Corporate Governance on Return on Assets (ROA) of Listed Information Technology Companies in Bangladesh - Md. Hossain; Md. Islam; Kamrun Naher (International Journal of Management, Accounting and Economics)
The study attempts to investigate the impact of corporate governance (CG) attributes on return on assets (ROA) of listed information technology companies in Bangladeshi. Secondary sources of data over the period of 5 years from 2018 to 2022 collected from Dhaka Stock Exchange (DSE) of the sample companies are used to analyze and mean, standard deviation, VIF, maximum, minimum and multiple regression techniques are applied to reach the objectives of the study. The results represent that there is a strong positive influence of corporate on ROA. Board size and nomination and remuneration committee are positively associated with ROA at 5% level of significance. On the other hand, a significant negative relationship between board independence and firm size proxied by total assets and ROA is seen. Audit committee independent, firm age, board meeting and firm performance of information technology listed companies are not statistically significantly related. The results of the study are more effective to management, shareholders, creditors and potential investors to make a useful decision for the companies.